Implementación de una pico central hidroeléctrica mediante una turbina turgo de baja potencia en el barrio Guadalupe - Tapia Villamarin, Antonio Agustin (2022)
Currently, microgeneration projects have been developed, especially in places that due to their geographical conditions prevent access to electricity supply by distribution companies, thus contributing to the use of renewable energy sources. In the present project, the house located in the Guadalupe neighborhood, lacks the supply of electricity, which by installing an electricity generation system will benefit the users who reside in the house. The generation system is made up of a 25-liter catchment reservoir, a low-power Turgo-type turbine, a single-phase generator that helps convert mechanical energy to electrical energy and consists of a control system for parameter verification. system generation.